PENGENDALIAN PERSEDIAN PAKAN AYAM PETELUR MENGGUNAKAN METODE EONOMIC ORDER QUANTITY (EOQ) PADA PETERNAKAN XYZ DI BANYUWANGI - Agustin, Refika Neni; Dyah, Herdiana; Yusuf, Muhammad (Matrik : Jurnal Manajemen dan Teknik Industri Produksi, 2024)
Delays in the supply of chicken feed at XYZ Farm resulted in a decrease in chicken egg productivity, resulting in chicken death. To ensure that production runs smoothly, XYZ Farms must guarantee the availability of raw materials for chicken feed. The aim of this research is to determine the ideal number of orders for chicken feed supplies to minimize feed shortages due to delivery delays. This research applies the Economic Order Quantity (EOQ) method to help XYZ farms manage the purchase of raw materials for chicken feed, and Single Exponential Smoothing to forecast supplies that are updated continuously by considering the latest data. The forecasting calculation uses an accuracy of 0.6 for the need for katul, corn and concentrate in January 2024. The results of the Economic Order Quantity (EOQ) calculation show that the optimal order for Katul is 6,702 kg, corn 29,190 kg, concentrate 25,402 kg. Orders are made 4 times a month, and Reorder Point is made when 1,586 kg of katul remains, 6,494 kg of corn and 8,742 kg of concentrate. Reordering or Reorder Point (ROP) is needed to overcome the potential for stock out during lead time TRANSLATE with x English Arabic Hebrew Polish Bulgarian Hindi Portuguese Catalan Hmong Daw Romanian Chinese Simplified Hungarian Russian Chinese Traditional Indonesian Slovak Czech Italian Slovenian Danish Japanese Spanish Dutch Klingon Swedish English Korean Thai Estonian Latvian Turkish Finnish Lithuanian Ukrainian French Malay Urdu German Maltese Vietnamese Greek Norwegian Welsh Haitian Creole Persian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster Portal Back //